Polymorphisms in the HTR2A and HTR3A Genes Contribute to Pain in TMD Myalgia - Sofia Louca Jounger; Sofia Louca Jounger; Nikolaos Christidis; Nikolaos Christidis; Britt Hedenberg-Magnusson; Britt Hedenberg-Magnusson; Britt Hedenberg-Magnusson; Thomas List; Thomas List; Peter Svensson; Peter Svensson; Peter Svensson; et al. (Frontiers Media S.A., 2021)
Background: The aim of this study was to investigate if single nucleotide polymorphisms (SNPs) related to monoaminergic neurotransmission, in particular the serotonergic pathway, contribute to pain perception in patients with temporomandibular disorder (TMD) myalgia and if there is a correlation to jaw function as well as psychosocial factors such as stress, anxiety and depression.Materials and Methods: One hundred and seventeen individuals with TMD myalgia were included. A venous blood or saliva sample was taken for genetic analyses and genotyped regarding HTR2A (rs9316233) HTR3A (rs1062613), HTR3B (rs1176744), SERT (5-HTTLPR) and COMT (rs4680). A clinical examination according to Diagnostic Criteria for TMD (DC/TMD) was performed and axis II data (psychosocial factors) were compared between participants with different genotypes for each gene using Kruskall-Wallis test. The characteristic pain intensity (CPI) was tested for correlations to scores for the Perceived Stress Scale, Generalized Anxiety Disorder, and Patient Health Questionnaires using Spearman's rank correlation test with Bonferroni correction for multiple testing. To further explore data factor analysis was performed to identify latent factors associated to the outcome variables.Results: Participants carrying at least one copy of the rare allele of the HTR2A (rs9316233) and HTR3A (rs1062613) had higher CPI compared with the participants with the homozygous common genotype (P = 0.042 and P = 0.024, respectively). Correlation analyses showed several significant positive correlations between CPI on one hand, and self-reported psychosocial distress and jaw function on the other hand for several genotypes that mostly were weak to moderate. The factor analysis identified two latent variables. One was positively correlated to the HTR3B gene, jaw function and self-reported parafunctions, and the other was positively correlated to psychological distress and negatively correlated to SERT.Conclusion: Taken together, the polymorphism rs1062613 in the HTR3A gene contributes to pain intensity in TMD myalgia. This together with positive interactions between pain variables and psychological factors in genotypes strengthens that pain and psychological distress are related. Further research is needed to explore this as well as the influence of gene-to-gene interactions on pain and psychological distress.